The Miserable Plight of Women in the Novels of M. R. Anand: Exploring the Oppression of Women in M. R. Anand's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Mulk Raj Anand, a socially committed novelist, has produced a good deal about the miserable plight of women in his novels. In his first novel Untouchable, the miserable plight of a woman has been best portrayed by him. Anand has stressed in his Old myth new myth recital verses Novel, the need for effecting a synthesis between tradition and modernity in novel form. He is conscious of the Hazards involved in keeping up the spirit of the old myths sustained in the contemporary idiom. Mulk Raj Anand has, in his novel taken a bold stand on behalf of millions of Indian women tortured and hounded by unsympathetic husbands, crafty in-laws, fault-finding and censorious kith and kin and above all, by deep seated guilt-feeling and self-accusing remorsefulness on the part of the woman, born out of centuries of psychological subjugation and bombardment.